Female Age at Marriage and Their Fertility in Tharu Community - Yadav, Rajkumar (Academic Voices: A Multidisciplinary Journal, 2014)
The main objective of this article is to study the age at marriage and their fertility (CEB) based on secondary data. The data were collected by M.A. Population Studies student Mr. Pramanand Chaudhary. He had selected the Tharu community of ward no.5,6 and 8 of Sundarpur VDC of Sarlahi district as a study area in 2006. This article tries to deal with age group, educational status, occupational status, types of family of respondents and their mean age at marriage. Similarly age at marriage educational status, occupational status of respondents and their mean children ever born (CEB) from the selected respondents. Household and respondents were selected with the help of purposive method where the prevalence of the female age at marriage in Tharu community was high. Collected data were analyzed on the basis of table, frequency distribution, percentage and simple statistics. Academic Voices, Vol. 3, No. 1, 2013, Pages 33-39 DOI: http://dx.doi.org/10.3126/av.v3i1.9982